Evolution and Domestication of a Novel Biosynthetic Gene Cluster Contributing to the Flavonoid Metabolism and High‐Altitude Adaptability of Plants in the Fagopyrum Genus - Xu Huang; Yuqi He; Kaixuan Zhang; Yaliang Shi; Hui Zhao; Dili Lai; Hao Lin; Xiangru Wang; Zhimin Yang; Yawen Xiao; Wei Li; Yinan Ouyang; et al. (Advanced Science, 2024)
Abstract The diversity of secondary metabolites is an important means for plants to cope with the complex and ever‐changing terrestrial environment. Plant biosynthetic gene clusters (BGCs) are crucial for the biosynthesis of secondary metabolites. The domestication and evolution of BGCs and how they affect plant secondary metabolites biosynthesis and environmental adaptation are still not fully understood. Buckwheat exhibits strong resistance and abundant secondary metabolites, especially flavonoids, allowing it to thrive in harsh environments. A non‐canonical BGC named UFGT3 cluster is identified, which comprises a phosphorylase kinase (PAK), two transcription factors (MADS1/2), and a glycosyltransferase (UFGT3), forming a complete molecular regulatory module involved in flavonoid biosynthesis. This cluster is selected during Tartary buckwheat domestication and is widely present in species of the Fagopyrum genus. In wild relatives of cultivated buckwheat, a gene encoding anthocyanin glycosyltransferase (AGT), which glycosylates pelargonidin into pelargonidin‐3‐O‐glucoside, is found inserted into this cluster. The pelargonidin‐3‐O‐glucoside can help plants resist UV stress, endowing wild relatives with stronger high‐altitude adaptability. This study provides a new research paradigm for the evolutionary dynamics of plant BGCs, and offers new perspectives for exploring the mechanism of plant ecological adaptability driven by environmental stress through the synthesis of secondary metabolites.